Family associationism as a place for the promotion of the human being - Crimì, Pinella (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Family associationism is that particular form of associationism characterised by the initiative of families, who ‘by binding together in associative forms, play an active role in civil society, planning and implementing interventions that support them, according to a specifically family code, in the performance of daily and exceptional tasks, or made necessary by situations of particular hardship’ (Carrà Mittini, 2008:5). These are, therefore, associative forms that respond to the needs of families and, at the same time, make possible the generative capacity proper to the family dimension. Families, if put in a position to realise their relational identity, vertically and horizontally, become bearers of the common good for the territories in which they live. Indeed, the families that promote associations put themselves at the service of the entire social fabric, in the manner proper to the relationship between genders and generations.